PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS DAN SELF-CONCEPT SISWA MELALUI MODEL BLENDED LEARNING - Supartini, Reny; Qotrunithra Bilqis Aria; Melinda Putri Mubarika (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2024)
In the context of 21st century learning and the challenges of the COVID-19 pandemic, blended learning is a relevant solution because it integrates technology to support interactive learning. Apart from that, the blended learning model has a positive effect on mathematical critical thinking abilities and self-concept, but in reality, students' mathematical critical thinking abilities and self-concept in Indonesia are still relatively low. This research aims to improve critical mathematical thinking skills, self-concept and analyze the positive correlation between students' critical thinking skills and self-concept using the blended learning model. This research refers to a quantitative approach using quasi experimental design. The subjects of this research were class X Science students at SMA Negeri 16 Bandung. Divided into 30 students for the experimental group and 30 students for the control class. Research data was obtained through mathematical critical thinking ability tests and self-concept questionnaires. The results of the research show 1) the increase in mathematical thinking skills of students who received the blended learning model was higher than students who received the regular learning model 2) the self-concept of students who received the blended learning model was better than students who received the regular learning model 3) there was a positive correlation between critical thinking abilities and self-concept of students who receive the blended learning model. The results of this research can be used as a basis for planning more effective teaching by adopting a blended learning model to maximize students' learning potential cognitively and affectively.